Wing Color of Monarch Butterflies (Danaus plexippus) in Eastern North America across Life Stages: Migrants Are "Redder" than Breeding and Overwintering Stages. (5th February 2009) - Davis Davis, Andrew K. Andrew K.
Abstract : Monarch butterflies are famous among insects for their unique migration in eastern North America to overwinter sites in Mexico and their bright orange wing color, which has an aposematic function. While capturing migrating monarchs in northeast Georgia, USA, I noticed that many appeared to have unusually deep orange wings. I initiated the current study to compare wing hues (obtained using image analysis of scanned wings) of migrants (captured in 2005 and 2008) to samples of breeding and overwintering monarchs. Consistent with initial observations, migrants had significantly lower orange hues (reflecting deeper, redder orange colors) than breeding and overwintering monarchs. There was also a difference in hue between sexes and a relationship with wing size, such that larger monarchs had deeper, redder hues. The reasons for the color difference of migrants are not apparent, but one possibility is that the longer-lived migrant generation has denser scalation to allow for scale loss over their lifespan. Alternatively, this effect could be confined to the subpopulation of monarchs in the Southeastern United States, which may not be well represented at the Mexican overwintering sites. In any case, this discovery highlights the many questions emerging on the significance of wing color variation in this species.